Financial System Soundness in the Caribbean : An Initial Assessment - Cherebin, Desiree (IMF Working Papers; Working Paper ;, 2001)
A survey of the financial systems of Caribbean countries reveals systems dominated by banks, with services widely available. Jamaica is the only country to have experienced a financial crisis. The paper describes recent improvements in the regulatory framework, and examines factors, which affect the soundness of the financial system, using both intuitive and econometric methodologies. The study identifies regulatory improvements that are needed, as well as additional data and analysis required to complete the assessment, which revealed no new threats to the financial system.